Geographical and Literary Lineage In Te Works of Salman Rushdie: Exploring the Multiple Loyalties and Identities in Salman Rushdie's Works (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Michael J. Sandel in his book entitled Democracy's Discontent: America in Search ofa Public Philosophy writes: The global media and markets that shape our livesbeckon us to a world beyond boundaries and belonging. But the civic resourceswe need to in the places and stories, memories and meanings, incidents andidentities, that situate us in the world and give our lives their moralparticularity. (349) This does not rule out global systems but posits anetwork of the global, the national and the local. In it, while weremain encumbered in our local communities we also recognize other loyalties,and negotiate our way intelligently between them. To quote Sandel again, Self government today requires a politics that playsitself out in a multiplicity of settings, from neighborhoods to nations to theworld as a whole ... The civic virtue distinctive to our time is the capacityto negotiate our way among the sometimes overlapping, sometimes conflictingobligations that claim us, and to live with the tension to which multipleloyalties give rise. (350) Salman Rushdie could be best described as havingmultiple loyalties, even multiple belongings - to India, to Britain, to theworld - rather than as having none at all. Pico Iyer, a dislocated, displaced,and deracinated man, rightly salutes his fellows when he describes Rushdie as'a connoisseur of dislocation' (148), and Michael Ondaatje as coming from afamily of' deracinated cosmopolitans' (136).